(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article examines the emergence and development of longreads in the landscape of online journalism in Uzbekistan. Long reads, characterized by their comprehensiveness and in-depth exploration of a variety of topics, have gained attention as an important tool for storytelling and investigative journalism. Driven by a desire to present nuanced perspectives outside of traditional news formats, longreads in Uzbekistan have evolved to address complex social, cultural, and historical issues. This study examines the origins, characteristics, impact, problems, and future prospects of long-term studies in Uzbekistan and shows how they contribute to a deeper understanding of social issues and strengthen public discourse in the digital age.